Characterization of the regulation mechanism of grapevine microRNA172 family members during flower development - Sun, Xin (BMC Plant Biol, 2020)
BACKGROUND: Grapevine (Vitis vinifera L.), which has important nutritional values and health benefits, is one of the most economically important fruit crops cultivated worldwide. Several studies showed a large number of microRNAs (VvmiRNAs) involved in the modulation of grape growth and development, and many VvmiRNA families have multiple members. However, the way by which various members from the same miRNA family work is unclear, particularly in grapes. RESULTS: In this study, an important conserved VvmiR172 family (VvmiR172s) and their targets were set as a good example for elucidating the interaction degree, mechanism, and spatio-temporal traits of diverse members from the same miRNA family. miR-RACE and Stem-loop RT-PCR were used to identify the spatio-temporal expressions of various members of VvmiR172s; together with RLM-RACE, PPM-RACE, Western blot, transgenic technologies, their interaction degree, and regulation mechanism were further validated. The expression of VvmiR172c was significantly higher than that of VvmiR172a, b, and d and showed a positive correlation with the abundance of VvAP2 cleavage products. These findings indicated that VvmiR172c might be one of the main action factors of the VvmiR172 family in flower development. The ability of VvmiR172c to cleave target genes differed due to divergence in complementary degree with VvAP2 and expression levels of various members. In VvmiR172 transgenic lines, we observed that 35S::VvmiR172c resulted in the earliest and abundant flowering, indicating the strong function of VvmiR172c. In contrast, the non-significant phenotypic changes were detected in the VvAP2 transgenic lines. The qRT-PCR and Western bolt results demonstrated that VvmiR172c plays a major role in targeting VvAP2. CONCLUSIONS: VvmiR172 up-regulated the expression of NtFT and decreased the expression of NtFLC. The up/down regulation of VvmiR172c was the most pronounced. The functions of four VvmiR172 members in grape differed, and miR172c had the strongest regulation on AP2.